Post-Semiotics of Da'wah Communication in Interpreting Signs of Religious Culture - Dindin Dimyati; Roro Retno Wulan; Dudi Rustandi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
Religious cultural artefacts such as the cap (peci), Koko shirt, turban, sarong, or the diction of ustadz and Islamic boarding schools are part of the power dynamics in the late 2021 and early 2022 abuse cases. This research aims to interpret the da'wah communication messages implied in religious cultural artefacts, as well as dismantle and restore the meaning of religious cultural symbols, in order to maintain and protect the degree of da'wah. A critical paradigm with a post semiotic (hyper semiotic) approach was used in the research. According to the findings of the study, the position of religious symbols in semiotics has noble values in the context of da'wah. However, it is an ideological tool for worshippers of desire to achieve their individual goals in the context of most semiotics. The artefact is shrouded in libido ideology. The authors' research bridges the problem of meaning, which is frequently generalised in everyday life, so that people can see clearly and wisely about this issue. Critical da'wah communication can help to develop this wisdom and policy.